The impact of weekly semaglutide, a glucagon-like peptide-1 agonist, on kidney outcomes in adults with type 2 diabetes mellitus - Ahmad A Algarni; Fahad S Alqarni; Hanin A Shalaby (Journal of Family Medicine and Primary Care, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder associated with kidney complications. This study aims to investigate the effects of weekly subcutaneous semaglutide, a GLP-1 agonist, on kidney outcomes. Methods: This retrospective cohort study was conducted in nephrology and endocrinology clinics at KFAFH from March 2022 to February 2023. The sample size was determined based on hospital records, and randomly selected patients who met the inclusion criteria were included. The inclusion criteria included adults with T2DM who were on weekly subcutaneous semaglutide for 6 months or longer. Patients with type 1 diabetes mellitus, pregnant or gestational diabetes patients, individuals who added other antidiabetic medications during the study period, and participants who refused to be involved were excluded from the study. Results: The study included participants aged between 42 and 85 years, with a mean age of 65.38 years, and the majority (58.7%) were males. There was a significant weight and BMI reduction observed in all patients, with P values <0.001 for both. The average weight reduction was 2.97 kg (SD = 2.34, 95% CI 1.65–3.30), and the average Body (BMI) reduction was 1.16 (SD = 0.91, 95% CI 1.03–1.29). A vast majority of participants (98.5%) reported a weight loss of at least 1 kg, and 13.8% of participants experienced a change in BMI category from higher to lower. No patients reported an increase in the BMI category. There was a significant reduction in glycohemoglobin (HbA1c) measurements from 9.18 pretreatment to 8.13 posttreatment, with an average reduction of 1.05 units (SD = 1.84, 95% CI 0.79–1.31). The majority of participants (70.9%) reported a reduction in HbA1c of at least 0.1 unit. Although there was a slight decrease in estimated glomerular filtration rate (eGFR) values on average (1.35 units), the change was not statistically significant (P = 0.059). More than half of the participants (51.5%) reported an increase in eGFR, 45.4% reported a decrease, and 3.1% reported no change. There was a statistically significant reduction in urinary albumin-to-creatinine ratio (UACR) values from a median of 5.97 pretreatment to a median of 5.60 post-treatment. The median decrease was 0.72 units, with one-third (33.3%) reporting an increase and two-thirds (66.7%) reporting a decrease in values. The correlation analysis revealed no significant association between the total quantity of semaglutide taken and the magnitude of changes. Conclusion: Our study on the impact of weekly semaglutide in adults with T2DM reveals positive effects on kidney outcomes, including weight loss, glycemic control and improved urine albumin creatine ratio, and a reduced risk of nephropathy. These findings highlight the potential of semaglutide as a safe and effective treatment option for improving renal health in individuals with T2DM.